2022
DOI: 10.1021/acs.jpcc.1c05812
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Kinetics of Energetic CL-20/BTF Cocrystal Induced by Strong Intermolecular Coupling

Abstract: Energetic cocrystals are an attractive new family of explosives with a potential for high energy and low sensitivity. The practical application of cocrystal explosives highly requires in-depth understanding of their thermal kinetic behavior, but the relevant research is still rare. In this study, we selected CL-20/BTF (2,4,6,8,10,12-hexanitrohexaazaisowurtzitane/benzotrifuroxan) cocrystal as a typical cocrystal explosive to investigate its thermal kinetics and decomposition mechanism. The thermal behavior of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The results showed that the first, second, and third processes were all not single reaction pathways, as explained earlier. 27 From the values of DH 1 , DH 2 , and DH 3 , the relative contributions of all individual processes to the overall process were calculated as À1.6 AE 0.4%, 79.3 AE 3%, and 22.3 AE 2%, respectively. Similar contributions were obtained regardless of the heating rate, thus supporting the fact that the different processes occurred independently and that the deconvolution procedure was reasonable.…”
Section: Deconvolution Of the Overlapping Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the first, second, and third processes were all not single reaction pathways, as explained earlier. 27 From the values of DH 1 , DH 2 , and DH 3 , the relative contributions of all individual processes to the overall process were calculated as À1.6 AE 0.4%, 79.3 AE 3%, and 22.3 AE 2%, respectively. Similar contributions were obtained regardless of the heating rate, thus supporting the fact that the different processes occurred independently and that the deconvolution procedure was reasonable.…”
Section: Deconvolution Of the Overlapping Reactionsmentioning
confidence: 99%
“…According to them, the decomposition mechanism of strong intermolecularly coupled CL-20 and BTF molecules resulted in parallel reaction pathways of the thermal kinetics of CL-20/BTF cocrystals. 27 Since the groups (2) and (3) of CL-20-based cocrystals have melting points, their thermal kinetics behaviors are distinct from those of groups (1) and (4). It was reported that the low-melting-point components of CL-20-based cocrystals having melting points evaporated when heated under isothermal and unsealed conditions, leaving g-CL-20 or amorphous CL-20.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in situ infrared spectroscopy was performed to detect the molecular evolution of CL-20/BTF cocrystal during thermal decomposition, which is helpful to understand the origin of its thermal kinetics. It is found that the unique decomposition mechanism of strong intermolecular coupling between CL-20 and BTF molecules is responsible for the parallel reaction paths of the thermal kinetics of the CL-20/BTF cocrystal [134].…”
Section: Cocrystals Of Cl-20 With Btfmentioning
confidence: 99%
“…Azole-based energetic cocrystals have also been reported, such as 5,5′-dinitro-3,3′-bi-1,2,4-triazole (DNBT) with 5-amino-3-nitro-1,2,4-triazole (ANTA) and 3,6-dinitropyrazolo­[4,3- c ]-pyrazole (DNPP) with 3,4-dinitropyrazole (3,4-DNP), which adopts a 2:1 molar ratio with high crystallographic densities varying from 1.858 to 1.889 g cm –3 . Recently, several cocrystals have been reported based on CL-20, BTF, and HMX with different coformers. In 2022, Bellas and Matzger reported cocrystals based on an energetic oxidizing salt to achieve a melt-castable energetic material . These studies have emphasized that cocrystallization is a valuable technique for enhancing the performance of explosives and pioneered the way for tailored energetic materials and further motivated the exploration of a library of energetic components for cocrystallization and rational design.…”
Section: Introductionmentioning
confidence: 99%